Delivering of Proteins to the Plant Vacuole-An Update - Claudia Pereira (2014)
Trafficking of soluble cargo to the vacuole is far from being a closed issue as it can occur by different routes and involve different intermediates. The textbook view of proteins being sorted at the post-Golgi level to the lytic vacuole via the pre-vacuole or to the protein storage vacuole mediated by dense vesicles is now challenged as novel routes are being disclosed and vacuoles with intermediate characteristics described. The identification of Vacuolar Sorting Determinants is a key signature to understand protein trafficking to the vacuole. Despite the long established vacuolar signals, some others have been described in the last few years, with different properties that can be specific for some cells or some types of vacuoles. There are also reports of proteins having two different vacuolar signals and their significance is questionable: a way to increase the efficiency of the sorting or different sorting depending on the protein roles in a specific context? Along came the idea of differential vacuolar sorting, suggesting a possible specialization of the trafficking pathways according to the type of cell and specific needs. In this review, we show the recent advances in the field and focus on different aspects of protein trafficking to the vacuoles.